A Digital Economy Perspective: Research on Legal Issues of Fintech Regulation - Yucheng Lei (Law and Economy, 2022)
The Internet digital economy is reshaping the global financial system with an irreversible trend, driving the transformation and development of financial technology. Due to the professional complexity and cross-border integration of financial technology, while improving the efficiency of traditional financial operations and reducing financial transaction costs, it also poses new challenges to Chinese regulatory authorities. In view of this, it is necessary to understand the development status of financial technology, clarify the regulatory subjects and principles of financial technology supervision, and sort out and summarize the existing regulatory model and its shortcomings. Finally, I will give advice on the problems existing in the practice of financial technology supervision, and theoretical support is put forward for improving the legal system of financial supervision, so as to promote the healthy development of financial technology.